An investigation of elt teachers' perceptions of digital technology integration via samr model in the 21st century education system - Orak, Suheyla Demirkol (IGI Global, 2023)
It is difficult for educators to teach young students to keep up with 21st-century education demands, even while the 21st century demands that learners be digitally savvy and self-driven to cope with technological innovation. Digital technology integration into the courses, however, can be thought of as the most time-appropriate and modern practice of the teaching-learning process, compared to other ways, in order to educate the students as adaptive to the needs of the 21st century. In particular, the SAMR Model is the most direct way to invest, gate teachers' perspective and technology integration levels because one of the needs of the 21st-century ELT is to stay up with the century and integrate digital sources into the lessons. This chapter intends to create a procedural connection between aspirations of the 21st century and their collaboration with the adoption of digital technology into activities. The SAMR Model and the function of teacher perceptions, as established by the literature, are also defined in the study along with some suggestions. Copyright © 2023, IGI Global. Copying or distributing in print or electronic forms without written permission of IGI Global is prohibited. © 2023 by IGI Global. All rights reserved.